The use of implementation science theoretical approaches in hybrid effectiveness-implementation type 1 randomised trials of healthcare interventions: A scoping review - Orly Atzmon; Meagan E. Crowther; Bei Bei; Denise A. O’Connor (Implementation Science)
Abstract Background Hybrid type 1 effectiveness-implementation randomised controlled trials (RCTs) aim to accelerate the translation of proven clinical interventions into routine care by concurrently investigating the effectiveness of clinical interventions and the context for real-world implementation. Hybrid type 1 RCTs can make use of implementation science theoretical approaches (i.e., theories, models, and frameworks) to understand barriers and facilitators to sustainable implementation of clinical interventions; however, the extent to which these approaches have been used in hybrid type 1 RCTs has not been systematically investigated. This scoping review aimed to investigate the extent to which implementation science theoretical approaches have been used in hybrid type 1 RCTs of healthcare interventions and describe which approaches have been reported and how they have been used. Methods The review was conducted in accordance with the pre-registered protocol ( https://doi.org/10.17605/OSF.IO/CJ8A7 ). Searches of six electronic databases were conducted for published hybrid type 1 RCTs evaluating any clinical intervention in any healthcare setting. The included trials were full-text, peer-reviewed primary research articles written in English, and reporting the findings of hybrid type 1 RCTs of healthcare interventions. Non-English language reports, reviews, protocols without a linked trial results report, methodological papers, opinion pieces, commentaries, books/book chapters, dissertations, and conference abstracts were excluded. Two reviewers independently selected studies, extracted data, and assessed use of theoretical approach/es. Results We identified 8,878 citations, screened 673 full-text records, and included 37 trials. Most trials were conducted in North America (68%), investigating clinical interventions for mental health problems (32%) in adults (43%). Twenty-eight (76%) trials cited use of at least one theoretical approach. The most common was the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework (43%). Theoretical approaches were most often applied (62%) to justify the implementation study design, guide selection of study materials or analyse implementation outcomes. Conclusion The majority of published hybrid type 1 effectiveness-implementation RCTs of healthcare interventions report using at least one theoretical approach to explore the context for implementation. Use of implementation science theories, models, and/or frameworks to understand the barriers and facilitators to implementation and sustainability of proven clinical interventions is likely to accelerate future translation of evidence-based practices into routine care and thus optimise patient outcomes.